2021
DOI: 10.3390/en14217081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Countdown Signal Timers on Driving Behavior and Road Safety

Abstract: This article describes the safety and effectiveness issues related to signal countdown timers (SCT). These devices are used in many countries around the world. The impact of these devices on road safety and the effectiveness of traffic lights is presented. During a literature review, more than 18 aspects of device use were recognized. The research involved measurements carried out at three intersections in Płock (Poland). The initial and final period of the green signal for vehicles was analyzed. Headways, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Several studies referred to selected problems in the reconstruction of road accidents [5,22,28]. A separate group of papers analyzed selected aspects of road infrastructure and traffic control [3,6,23,24]. All of the data show that the weakest link in the road safety system is man, and more specifically, vehicle drivers.…”
Section: A Brief Overview Of the Content Of This Special Issuementioning
confidence: 99%
“…Several studies referred to selected problems in the reconstruction of road accidents [5,22,28]. A separate group of papers analyzed selected aspects of road infrastructure and traffic control [3,6,23,24]. All of the data show that the weakest link in the road safety system is man, and more specifically, vehicle drivers.…”
Section: A Brief Overview Of the Content Of This Special Issuementioning
confidence: 99%
“…From the perspective of vehicles, technologies such as emission after-treatment and vehicle fleet electrification can lead to a substantial decrease in emissions and fuel consumption [ 4 , 5 , 6 , 7 , 8 ]. Methods that mitigate traffic congestion, such as adaptive signal timing control, countdown signal timers, predictive cruise control, and connected automated vehicles (CAVs) can also effectively control traffic emissions through shorter delays and less stop-and-go operations [ 9 , 10 , 11 , 12 ]. Compared to the above-mentioned methods, adopting ecological driving behaviour (eco-driving) is a more cost-effective method because it does not require the upgrade of the vehicle powertrain or the reconstruction of infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some studies have reported the positive effects of PSCTs on increasing pedestrian volume. Furthermore, research ( 8 , 10 , 21 ) has shown that the presence of a PSCTs increases pedestrian reaction time and also increases pedestrian speed ( 8 ). Besides, the number of pedestrians increased on the Flashing Green (or Amber or Flashing Don’t Walk) Signal by installing a PSCTs.…”
mentioning
confidence: 99%